The steps of kings: terraced landscapes in the Lake Pátzcuaro Basin, Michoacán, México - Pezzutti, Florencia Lorena, author; Pendell, Dustin L., advisor; Pritchett, James, committee member; Shields, Martin, committee member (Colorado State University. Libraries, 2010)
This thesis uses a landscape approach incorporating landesque capital as statecraft to relate agricultural intensification and state formation theories using data collected from the former island of Apúpato, in the Lake Pátzcuaro Basin, Michoacán, México. Apúpato is located in the geo-political core of the Purépecha Empire, south of Tzintzuntzan, the empire's capital. Apúpato was an important Purépecha island belonging to the Canzonci [Purépecha emperor] and was used as a ritual center, an imperial treasury, and for feasts and expeditions (RM 2008: page) This thesis incorporates recent archaeological investigation, including full coverage settlement pattern survey, geoarchaeology, and remote sensing/ARCGIS, which documented patterns of settlements, confirmed the presence of terraces, and the general landscape development of the former island. This thesis documents and analyzes, for the first time, agricultural terraces in the former island of Apúpato. The most common form of agricultural intensification is terrace agriculture (Donkin 1979) which is linked to the development of social complexity in middle range societies, and states and empires (Fisher et al. 2003). For Mesoamerica, terraces are a fundamental characteristic of ancient social complexity, and continued to be used post-Conquest (A.D. 1520). In the Lake Pátzcuaro basin, agricultural intensification was an important component of state formation in the lake Pátzcuaro basin (Pollard 1993) exemplified by raised field systems and by the construction of terraces to repair Classic period land degradation (A.D 300-800) and to improve productivity of seed crops (Fisher et al 2003; Fisher 2005). This thesis examines the implications of agricultural intensification and state formation in Mesoamerica, using terrace data collected from the former island of Apúpato. The terrace system documented on Apúpato represents a refugia for the Purépecha built environment in the Lake Pátzcuaro Basin, since the Apúpato island setting remained an island for hundreds of years, helping keep Apúpato protected and isolated from the consequences of the European conquest. The terraces documented in the former island of Apúpato are analyzed in terms of their form, function, and construction development for the first time in the Lake Pátzcuaro Basin.
Department Head: Stephen P. Davies.